Finite element analysis of heat transfer through timber elements exposed to fire. (15th July 2017) - Thi, V.D.; Khelifa, M.; Oudjene, M.; Ganaoui, M. El; Rogaume, Y.
Highlights: A thermal analysis of timber exposed to fire is performed. New thermo-physical properties in analogy the Eurocode 5 are adopted. A user-defined subroutine UMATHT is implemented in the Abaqus software. Abstract: Since timber is a combustible material, its safe use in construction will depend on a proper knowledge and modelling of the physical and chemical reactions involved in the pyrolysis, that affect the temperature growth and thus the performance of timber in fire. Based on the comprehensive one-dimensional analytical models of the pyrolysis available in the literature, it is required to implement a predictive FE model via a user-defined subroutine in the dedicated commercial software in order to describe more closely the real physical phenomena that undergo timber exposed to fire. This paper presents the implementation of the UMATHT subroutine in the Abaqus software. The obtained results showed a fairly good agreement with experimental ones from the literature. However, at this stage of the study the pyrolysis is taken into account implicitly in the developed UMATHT through gradually modified thermo-physical properties of the timber, as commonly adopted in the published literature. Work is now in progress to implement explicitly the different reactions of the pyrolysis in the developed UMATHT.